1924
DOI: 10.1002/cber.19240570419
|View full text |Cite
|
Sign up to set email alerts
|

Zur Kenntnis des mit Platinmohr dargestellten Dekahydro‐naphthalins. (VII. Mitteilung über Hydrierung aromatischer Verbindungen mit Hilfe von Platin.)

Abstract: Zu gleicher Zeit rnit unserer Untersuchungl) uber die Hydrierung des Naphthalins ist aus dem W i n d a u s schen Laboratorium eine vortreffliche Arbeit von W. H ii c k e l 2) hervorgegangen, ))Die Stereoisomerie des Dekahpdronaphthalins und seine; Derivatecc. Die Kenntnis der Polymethylene eird dadurch wesentlich gefordert. Nach W. H ii c k e 1 entsprechen die bekannten zwei isomeren D e k a h y d r oj 3n a p h t h o 1 e 3) nicht demselben Keton, sondern zwei isomeren f 3 -D e k a l o n e n , die als Abkgmmlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1924
1924
1957
1957

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Willstátter and Seitz (329) have found that a platinum catalyst rich in oxygen causes the formation of tetralin at room temperature; if the catalyst is poor in oxygen, decalin is formed directly, and no tetralin can be detected. The decalin so obtained has been shown to be the cis form (330). Maillard (204) has shown that hydrogenation of naphthalene at 20°C.…”
Section: Hydrogenation Of Naphthalenementioning
confidence: 98%
“…Willstátter and Seitz (329) have found that a platinum catalyst rich in oxygen causes the formation of tetralin at room temperature; if the catalyst is poor in oxygen, decalin is formed directly, and no tetralin can be detected. The decalin so obtained has been shown to be the cis form (330). Maillard (204) has shown that hydrogenation of naphthalene at 20°C.…”
Section: Hydrogenation Of Naphthalenementioning
confidence: 98%
“…The hydrogenation of naphthalene in glacial acetic acid on platinum black gives about a 5 per cent yield of irans-decalin (205) (this is more stereospecific than in the hydrogenation of 1,9-octalin). Similar hydrogenation with the Adams platinum oxide at 120 atm.…”
Section: H2 H H2 Hmentioning
confidence: 93%